2013
DOI: 10.1002/pssb.201248512
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of the first sharp diffraction peak in network glasses: Evidence for correlations with dynamic and rigidity properties

Abstract: Abstractmagnified imageThe structural and dynamical properties of densified sodium silicates are investigated using molecular dynamics (MD) simulations. From the analysis of the first sharp diffraction peak (FSDP) in the amorphous phase, it is shown that some of its characteristic parameters (position, width) in partial structure factors display minima in a certain pressure interval defining a window. The pressure window can be correlated with anomalies in transport properties (diffusion, viscosity) and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 50 publications
8
56
1
Order By: Relevance
“…The corresponding activation energies E A display a similar minimum with pressure 9 , and when represented as a function of the calculated number of constraints, it is found that the minimum in E A coincides with n c ¼ 3 (top inset of Fig. 5a).…”
Section: Glass Transition Cyclementioning
confidence: 63%
See 2 more Smart Citations
“…The corresponding activation energies E A display a similar minimum with pressure 9 , and when represented as a function of the calculated number of constraints, it is found that the minimum in E A coincides with n c ¼ 3 (top inset of Fig. 5a).…”
Section: Glass Transition Cyclementioning
confidence: 63%
“…The system under investigation is composed of 3,000 atoms that interact via a Born-Mayer pair-wise potential (J. Teter, unpublished results), which has been found to accurately reproduce experimental data on structure and dynamics [7][8][9] . Simulations have been performed both in (N, V, T) with 1.6 g cm À 3 oro4.2 g cm À 3 (for example, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation with chemical order is also debated by Boolchand and others who have emphasized the link between fragility minima and Figure 6. Correlation between relaxation properties, calculated diffusivity D (blue) and activation energy E A for diffusivity (red axis of the upper panels), and structural properties in the glassy state (black curve, width ∆k F SDP of the FSDP) in systems with changing pressure (2SiO 2 -Na 2 O, [69,70], left panels) or changing composition (As-Se, [71], right panels). Note that for As-Se, an opposite behavior for ∆k F SDP with composition is found from Reverse Monte Carlo [72].…”
Section: Qualitative Fragility Relationshipsmentioning
confidence: 99%
“…Neutron structure factor Figure 7 shows the total neutron structure factor for C-S-H as well as for the corresponding crystal and glass. Once again, the three structure factors do not show significant differences and are typical of those observed in silicate 36 and chalcogenide 37 glasses. It should be mentioned that the limited sizes of the simulated systems do not allow us to study large-scale correlations (large r, low Q).…”
Section: Medium-range Ordermentioning
confidence: 52%